Responsible innovation: Its role in an era of technological and regulatory transformation. Issue 1 (29th March 2021) - Tait, Joyce; Brown, Alex; Lalinde, Isabela Cabrera; Barlow, Daniel; Chiles, Matthew; Mason, Paul
Abstract: In the development of innovative technology products, companies of all sizes are being encouraged to innovate responsibly and regulators are encouraged to adapt their regulatory systems to be smarter, more proportionate and adaptive to the needs of innovative technologies. The British Standards Institution Responsible Innovation (RI) Guide (Publicly Available Specification [PAS] 440) is an industry‐wide standard relevant to both these policy trends. It supports companies by providing a framework to demonstrate the balance between the potential benefits and harms and, if necessary, to take action to maximise the benefits and/or minimise the harms. It includes guidance on engagement with stakeholders and will codify what stakeholders can expect from companies undertaking responsible innovation, paving the way to more harmonious relationships among stakeholders with differing interests and values. A cross‐sectoral survey of innovative companies showed that 90% favoured the development of such a standard. PAS 440 was also trialled in two early‐stage biotechnology companies and its expected benefits included contributing to coordinated responsible behaviour along a supply chain; better company and stakeholder understanding of the product properties; supporting decision‐making on whether or not to start a company; considering the risks of not developing the product and avoiding reputational risks. Benefits were expected to be increasingly significant as the RI standard becomes widely adopted.